Intraocular Pressure and Ocular Pulse Amplitude Comparisons in Different Types of Glaucoma Using Dynamic Contour Tonometry - Punjabi, Omar S.; Ho, Hoai-Ky V.; Kniestedt, Christoph; Bostrom, Alan G.; Stamper, Robert L.; Lin, Shan C. (Current eye research, 2006)
Purpose: To compare the intraocular pressures (IOP) and ocular pulse amplitudes (OPA) in patients with different types of glaucoma, ocular hypertension (OHT), and normal controls (NC) using dynamic contour tonometry (DCT) and the goldmann applanation tonometry (GAT). Methods: 906 eyes of 501 adult patients in the following five groups were included in this cross-sectional study: primary open angle glaucoma (POAG), normal tension glaucoma (NTG), Pseudoexfoliative Glaucoma (PXG), OHT, and NC. The following tests were performed simultaneously during a single visit: IOP using DCT and GAT; OPA using DCT and central corneal thickness (CCT) using ultrasound pachymetry. Mixed effects regression models were used to compare the DCT and GAT IOP measurements in the five groups; the effect of CCT on IOP and the relationship between OPA and IOP within each group. Results: DCT consistently had higher IOP values than GAT in POAG, PXG, NTG, and controls (p < 0.001) but not in OHT (p = 0.84). DCT IOP did not change while GAT IOP showed a non-significant increase (p = 0.09) with increased corneal thickness in each group. OPA was found to be highest in OHT (3.61 mmHg) and lowest in the control group (2.86 mmHg) and significantly increased with IOP in all groups. Conclusions: DCT measures an IOP that is significantly higher than GAT IOP in glaucoma and control subjects but not in ocular hypertensives. Furthermore, the DCT may measure an IOP that is independent of the CCT, which may not be true for the GAT, which increases with the CCT. OPA was highest in OHT and may be affected by the IOP.